2004
DOI: 10.1021/bi0496642
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structural Ramifications of a Hinge Domain in Apolipoprotein A-I Discoidal High-density Lipoproteins of Different Size

Abstract: Apolipoprotein (apo) A-I is the major protein constituent of human high-density lipoprotein (HDL) and is likely responsible for many of its anti-atherogenic properties. Since distinct HDL size subspecies may play different roles in interactions critical for these properties, a key question concerns how apoA-I can adjust its conformation in response to changes in HDL particle size. A prominent hypothesis states that apoA-I contains a flexible "hinge domain" that can associate/dissociate from the lipoprotein as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 39 publications
8
80
0
Order By: Relevance
“…The authors suggested that this region is responsible for absorbing changes in particle size by unfolding under conditions when lipid surface area is limiting. This is consistent with previous studies from our laboratory which used lipid-based fluorescence quenching agents to show that this same region changes its exposure to lipid when the particle diameter is reduced (Maiorano et al 2004).…”
Section: Introduction/brief Historysupporting
confidence: 92%
“…The authors suggested that this region is responsible for absorbing changes in particle size by unfolding under conditions when lipid surface area is limiting. This is consistent with previous studies from our laboratory which used lipid-based fluorescence quenching agents to show that this same region changes its exposure to lipid when the particle diameter is reduced (Maiorano et al 2004).…”
Section: Introduction/brief Historysupporting
confidence: 92%
“…The Belt model is characterized by a closed double belt conformation of the antiparallel apoA1 dimer encircling a lipid bilayer ( 9 ). Virtually all subsequent refi nements to models of nHDL (11)(12)(13)(14) have posited a closed apoA1 dimer in a belt confi guration that completely enshrines a central lipid bilayer, regardless of lipid composition. We recently used SANS with contrast variation to directly visu alize for the fi rst time the protein component of nHDL reconstituted with apoA1:POPC:cholesterol (1:100:10, Supplemental Material can be found at: micellar region).…”
Section: Discussion Of the Turtle Model In The Historical Context Of mentioning
confidence: 99%
“…Nevertheless, various models of nHDL have been proposed in the past ( 6,7 ), and they rely on biophysical, biochemical, and computer simulation studies [e.g., the Picket Fence model ( 8 ), the Belt model ( 9,10 ), the Hairpin Loop models (11)(12)(13), the Solar Flares model ( 14 ), the Double Super Helix model ( 15 ), and the Twisted Belt model ( 16,17 )]. All current models have in common an antiparallel orientation of the two apoA1 chains, but the overall conformation of apoA1 within the particle is still a matter of intense debate ( 18 ).…”
Section: Preparation Of Nhdl Dmpc With and Without Cholesterolmentioning
confidence: 99%
“…Recently, Maiorano and colleagues (7) proposed that apoA-I can adopt one of two possible extended ␣ helical conformations, including the extended belt model described above or a model wherein the apoA-I molecule loops back on itself, forming a "hairpin" structure ( Fig. 1).…”
mentioning
confidence: 99%